Evaluating the impact of pop-off mechanisms in boys with posterior urethral valves - Delefortrie, T.; Ferdynus, C.; Paye-Jaouen, A.; Michel, J. L.; Dobremez, E.; Peycelon, M.; El Ghoneimi, A.; Harper, L. (Frontiers in Pediatrics, 2022)
Introduction There have been several studies on the effect of pop-off mechanisms in boys with posterior ure-thral valves, but results are contradictory. We aimed to assess the effect of pop-off mechanisms on renal function in a large cohort of patients. Patients and method Boys with PUV with and without pop-off mechanisms (urinoma, VURD or giant bladder diverticula) were divided into three severity groups for renal function according to their nadir creatinine (low-risk NC < 35 μmol/L, intermediate-risk NC between 35 and 75 μmol/L, and high-risk NC > 75 μmol/L). We compared children with and children without pop-off mechanisms for mean renal function as well as patient distribution within each severity group. Results We included 137 boys of which 39 had a pop-off mechanism. Patients had complete data for at least 2 years follow-up. Though there was no significant statistical difference in mean renal func-tion between the pop-off and non-pop-off group, patient distribution within each severity group varied according to whether patients had a pop-off mechanism or not. a